Prevalensi Dan Faktor Risiko Infestasi Strongyle Pada Sapi Di Kebumen, Jawa Tengah: Prevalence and Risk Factors of Strongyle Infestation in Cattle in Kebumen, Central Java - Haryadi, Fathur Rohman; Dalimunthe, Naela Wanda Yusria; Andityas, Morsid; Ridlo, Muhammad Rosyid; Nesti, Dela Ria (Fakultas Peternakan Universitas Jambi, 2026)
Background: Strongyle infestation in cattle is a significant problem in the livestock sector, impacting animal health and productivity, and can even lead to death if continued. Furthermore, it impacts the economic well-being of livestock farmers. Strongyle's presence reduces livestock performance, triggering weight loss, digestive system disorders, and reduced meat production efficiency. The spread of Strongyle is influenced by multiple factors, including the environment, husbandry practices, and farm management. Purpose: This study aims to determine the prevalence and risk factors of Strongyle in cattle in Kebumen, Central Java. Methods: The cattle feces sampling method was purposive sampling, conducted door to door. The research sample consisted of 102 cattle feces examined by flotation method using saturated sugar solution as a flotation agent. The data were analyzed descriptively. Determination of infection risk factors was carried out using the chi-square test using SPSS 16.0 software. Results: The results of the study showed that the prevalence of Strongyle infestation in the digestive tract in cattle in Kebumen was 44.12%. The results of the calculation and descriptive analysis of the Chi-Square test showed that gender, age, and breed did not have a statistically significant relationship with worm infestation (p > 0.05). Conclusion: The conclusion of the study is that the prevalence of Strongyle infestation in the digestive tract in cattle in Kebumen is classified as moderate and Strongyle infestation is thought to be more influenced by environmental factors and maintenance management.